Analysis of the work Lienzos de la memoria (collection “Artistic and Cultural Activations in the Final Report of the Commission for the Clarification of Truth, Coexistence and Non-Repetition”) in light of the concept of face in Emmanuel Lévinas (REVISTA NODO, 2024)
The artistic project Lienzos de la memoria, led by the organization Casas de la Verdad con Sentido, of the Cultural and Artistic Strategy of the Truth Commission and carried out with the Grupo ProActo Teart Foundation, is found in the collection of Artistic and Cultural Activations in the Final Report of the Commission for the Clarification of Truth, Coexistence and Non-Repetition, as a space that symbolically recounts the internal armed conflict that lasted more than half a century in Colombia and that is still alive in some parts of the country.